Equivalence of measurements of carotid stenosis. A comparison of three methods on 1001 angiograms. European Carotid Surgery Trialists' Collaborative Group. - Rothwell, P; Gibson, R; Slattery, J; Sellar, R; Warlow, C (1994)
BACKGROUND AND PURPOSE: There is confusion about how carotid stenosis should be measured on angiograms. If the results of research based on different methods of measurement of stenosis are to be discussed and the results of clinical trials properly applied to routine clinical practice, measurements made by the different methods must be formally compared. METHODS: The method of measurement of stenosis used in the European Carotid Surgery Trial (ECST), that used in the North American Symptomatic Carotid Endarterectomy Trial (NASCET), and a method based on measurement of the common carotid (CC) artery lumen diameter were compared. Carotid stenosis was measured by two observers, working independently and using the three different methods of measurement, on the angiographic view of the symptomatic carotid stenosis that showed the most severe disease in 1001 patients from the ECST. RESULTS: The results of using the ECST and CC methods differed from those of using the NASCET method in the classification of stenoses as mild (0% to 29%), moderate (30% to 69%), or severe (70% to 99%) in 51% of measurements. The ECST and CC methods indicated that twice as many stenoses were severe as did the NASCET method, and classified less than a third of the number of stenoses as mild. The results of the ECST and CC methods differed from each other in 15% of measurements. The relations between measurements made by each method to those made by the others were approximately linear, so a simple equation could be derived to convert measurements made by one method to measurements made by the others. CONCLUSIONS: There were major and clinically important disparities between measurements of stenosis made using different methods of measurement on the same angiograms. However, it is possible to convert measurements made by one method to those of another using a simple arithmetic equation.